(untitled) (Archaeologia Adriatica, 2020)
The Vrbjanska Čuka archaeological site is a tell site of the type that is common in the Pelagonian region. It is located approximately 1.3 km south of Slavej and the same distance east of Vrbjani (Republic of North Macedonia). The site was excavated from 1979 to 1989, and new multidisciplinary research on the tell started in 2016. The recent archaeological excavations took place in a 15 x 10 m trench, where 2 houses with ovens, bins, railings and platforms in their interior were recorded. Typical characteristics of the Pelagonian Neolithic were observed in the material culture but also remains from the Classical antiquity and Medieval periods were documented. Besides the excavation and documentation of archaeological material, in 2016 an archaeobotanical analysis of organic samples was conducted, together with a geomagnetic survey of the whole area, digital topographic modelling of the tell and a 3D reconstruction of its appearance, and also an investigation of the prehistoric sites around Vrbjanska Čuka. This multidisciplinary approach provided new data and a more detailed understanding of the processes through which this settlement developed.